CHALLENGES, EMERGING TRENDS, AND FUTURE DEVELOPMENT OF REAL-TIME GIS: CHALLENGES, EMERGING TRENDS, AND FUTURE DEVELOPMENT OF REAL-TIME GIS - Dimanova, Donika; Kuzmanov, Zdravko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The paper examines the challenges, emerging trends, and future prospects for the development of real-time Geographic Information Systems (GIS). The first part analyzes the key challenges associated with the implementation and maintenance of such systems, including technical and infrastructural issues, data security and privacy, and the integration of heterogeneous data sources. The second part emphasizes future trends, such as the integration of artificial intelligence and machine learning, the advancement of 5G networks and the Internet of Things (IoT), cloud technologies, predictive analytics, as well as the expanded application of real-time GIS across various sectors, including healthcare, urban planning, energy, and agriculture. The main objective of the study is to outline the key directions for the development of real-time GIS and to highlight their importance for effective resource management, infrastructure oversight, and risk assessment in contemporary society.